1985
DOI: 10.1210/jcem-61-2-269
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Abnormalities of Myocardial Relaxation in Hypothyroidism

Abstract: Fifteen selected hypothyroid patients without symptoms or signs of cardiovascular disease and an equal number of matched control subjects underwent simultaneous recording of electrocardiogram and phono-, apex-, and echocardiography to assess dynamic systolic and diastolic left ventricular function. Both the systolic preejection period and the isovolumic relaxation period were significantly increased in the hypothyroid group. However, whereas the rate of myocardial contraction, assessed from the echocardiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 0 publications
3
22
0
Order By: Relevance
“…Abnormal left ventricular dimensions and asymmetrical septal thickening also abated. Such resolution of cardiac abnormalities after hormone therapy has been previously documented [8,10,12,18]. However, one notable exception in our patients was regional wall motion abnormality.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Abnormal left ventricular dimensions and asymmetrical septal thickening also abated. Such resolution of cardiac abnormalities after hormone therapy has been previously documented [8,10,12,18]. However, one notable exception in our patients was regional wall motion abnormality.…”
Section: Discussionsupporting
confidence: 82%
“…Pericardial effusion has long been known to be a feature of so-called myxedema heart [3]. However, it was the use of echocardiography that established the presence of not previously suspected lesions, indicated by such characteristics as thickening of the interventricular septum [9] and other abnormalities of cardiac muscle [12][13][14][15][16][17][18]. In our study, a wide variety of lesions were found in hypothyroid patients (Tables 1-3).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Cardiac output, stroke volume and plasma volume are reduced in hypothyroidism [6, 7], and myocardial contraction and relaxation rates are slowed [7, 8]. Thyroid hormone has been shown to affect calcium uptake by the sarcoplasmic reticulum, to stimulate plasma membrane Ca-ATPase activity and to increase voltage-dependent calcium channels in chick ventricular cells [3, 9].…”
Section: Introductionmentioning
confidence: 99%